Transitioning circular economy from policy to practice in Kenya - Muriithi, Joseph K.; Ngare, Innocent O. (Frontiers in Sustainability, 2023)
Policies are imperative in assessing how certain proposed actions or practises can be implemented. In the context of the circular economy, public policies have been influential in determining the way practises are adopted and implemented. In specific contexts, policies can be used to assess a country's preparedness to transition to the circular economy by examining how those that are formulated support the transition. This study examines Kenya's circular economy policy landscape by looking at the strides made by the country to embrace the concept and principles of the circular economy and focusing on the policies formulated so far. Using the thematic analysis approach, the study examines relevant circular economy laws, policies, and regulations to capture the initiatives the country has taken to embrace circular economy principles.The study's overall finding points to environmental sustainability, resource efficiency, sustainable economic development, and stakeholder engagement as the four primary policy areas shaping Kenya's transition to a circular economy. However, there persist certain obstacles to the effective implementation of circular economy principles. These challenges encompass the prevailing dominance of the government in the circular economy sector, which ought to be a collaborative endeavour involving both the private and public sectors. Furthermore, there is a scarcity of financing mechanisms to support circular economy initiatives, inadequate infrastructure to effectively implement circular economy practices, and a lack of capacity to propel progress in both the public and private sectors. Given that many of these challenges revolve around the financial aspect, the study recommends that the Kenyan government consider providing financial incentives to foster dynamism in harnessing the environmental and economic potential offered by the emerging circular economy.